Petition of the visitors and governors of William and Mary College (House document (Virginia. General Assembly. House of Delegates) ;, 1836)
1836? Petition of the Visitors and Governors of William and Mary College, to the Virginia General Assembly. The petition requested an additional endowment for improvements and needs.